Severity of COVID-19 after Vaccination among Hemodialysis Patients: An Observational Cohort Study. Issue 6 (June 2022) - Ashby, Damien R.; Caplin, Ben; Corbett, Richard W.; Asgari, Elham; Kumar, Nicola; Sarnowski, Alexander; Hull, Richard; Makanjuola, David; Cole, Nicholas; Chen, Jian; Nyberg, Sofia; McCafferty, Kieran; et al.
Visual Abstract: Abstract : Background and objectives: Patients receiving hemodialysis are at high risk from coronavirus disease 2019 (COVID-19) and demonstrate impaired immune responses to vaccines. There have been several descriptions of their immunologic responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination, but few studies have described the clinical efficacy of vaccination in patients on hemodialysis. Design, setting, participants, & measurements: In a multicenter observational study of the London hemodialysis population undergoing surveillance PCR testing during the period of vaccine rollout with BNT162b2 and AZD1222, all of those positive for SARS-CoV-2 were identified. Clinical outcomes were analyzed according to predictor variables, including vaccination status, using a mixed effects logistic regression model. Risk of infection was analyzed in a subgroup of the base population using a Cox proportional hazards model with vaccination status as a time-varying covariate. Results: SARS-CoV-2 infection was identified in 1323 patients of different ethnicities (Asian/other, 30%; Black, 38%; and White, 32%), including 1047 (79%) unvaccinated, 86 (7%) after first-dose vaccination, and 190 (14%) after second-dose vaccination. The majority of patients had a mild course; however, 515 (39%) were hospitalized, and 172 (13%) died. Older age, diabetes, and immune suppression were associated with greater illness severity. In regression models adjusted for age, comorbidity, and time period, prior two-dose vaccination was associated with a 75% (95% confidence interval, 56 to 86) lower risk of admission and 88% (95% confidence interval, 70 to 95) fewer deaths compared with unvaccinated patients. No loss of protection was seen in patients over 65 years or with increasing time since vaccination, and no difference was seen between vaccine types. Conclusions: These data demonstrate a substantially lower risk of severe COVID-19 after vaccination in patients on dialysis who become infected with SARS-CoV-2.